2014
DOI: 10.1016/j.bbamcr.2014.09.011
|View full text |Cite|
|
Sign up to set email alerts
|

The yeast model suggests the use of short peptides derived from mt LeuRS for the therapy of diseases due to mutations in several mt tRNAs

Abstract: We have previously established a yeast model of mitochondrial (mt) diseases. We showed that defective respiratory phenotypes due to point-mutations in mt tRNA(Leu(UUR)), tRNA(Ile) and tRNA(Val) could be relieved by overexpression of both cognate and non-cognate nuclearly encoded mt aminoacyl-tRNA synthetases (aaRS) LeuRS, IleRS and ValRS. More recently, we showed that the isolated carboxy-terminal domain (Cterm) of yeast mt LeuRS, and even short peptides derived from the human Cterm, have the same suppressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Importantly, the observation that the rescuing effect of the mt‐LeuRS‐derived sequences is exerted not only on the cognate mt‐tRNA Leu(UUR) but also on the non‐cognate mt‐tRNA Lys , led us to propose that these sequences may be active on a large spectrum of human mt‐tRNA mutants. Indeed, transfection of nucleotide sequences encoding for both β32_33 and β30_31 peptides has been demonstrated to be able to rescue the phenotype of a large panel of mt‐tRNA mutants in the yeast model 9 …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the observation that the rescuing effect of the mt‐LeuRS‐derived sequences is exerted not only on the cognate mt‐tRNA Leu(UUR) but also on the non‐cognate mt‐tRNA Lys , led us to propose that these sequences may be active on a large spectrum of human mt‐tRNA mutants. Indeed, transfection of nucleotide sequences encoding for both β32_33 and β30_31 peptides has been demonstrated to be able to rescue the phenotype of a large panel of mt‐tRNA mutants in the yeast model 9 …”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study is to evaluate the cellular internalization of multi-walled carbon nanotubes (MWCNTs) chemically conjugated or not with the peptide sequence previously demonstrated to suppress the defective growth phenotype due to mt tRNA mutations. Indeed studies on the yeast model have recently shown that overexpressed mt LeuRS-Cterm, β30_31 and β32_33 peptides (15 and 16 amino acids long, respectively) suppressed the respiratory defects due to mutations in mt tRNAs aminoacylated by class II, as well as class I mt aaRS 5,12 . The suppression capability of these plasmid constructs was also confirmed in human cells 10,11,13 .…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of the oligonucleotide sequences coding for the peptides β30_31 (MAVLINNKACGKIPV) or β32_33 (KKSFLSPRTALINFLV), comprised within the orthologous carboxy-terminal domain of human LeuRS, corrected the defects associated with several point mutations in yeast mt tRNA 5,12 . This activity has been obtained also in transfected cybrid lines bearing substitution in tRNA Leu(UUR) and tRNA Lys 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations